2000
DOI: 10.1309/428n-60xk-uq3q-bxlc
|View full text |Cite
|
Sign up to set email alerts
|

Poor Predictive Ability of Urinalysis and Microscopic Examination to Detect Urinary Tract Infection

Abstract: Results of urinalysis, particularly the leukocyte esterase and nitrite tests, often are used to determine whether treatment is needed or a culture will be performed in cases of suspected urinary tract infection. However, there is disagreement over the quality of urinalysis as a screening test for urinary tract infections. Final urine culture results (n = 225) were obtained from the clinical microbiology laboratory. Stepwise binary logistic regression was used to derive a model using presence of infection as de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 9 publications
2
25
1
2
Order By: Relevance
“…False negatives may be the result of a lack of dietary nitrate, dilution of the nitrite in the urine (such as with diuretics), or non-nitrate-reducing bacteria including Staphylococcus, Enterococcus, or Pseudomonas 16 . VanNostrand and colleagues 17 found that 78.9% of samples containing nitrate-reducing bacteria were actually negative for nitrite on the urine dipstick. Therefore the presence of nitrite has a high positive predictive value of 94% 18 , but in the absence of urinary nitrite a UTI cannot be ruled out.…”
Section: Urinalysis Part 1: Urine Dipstickmentioning
confidence: 99%
“…False negatives may be the result of a lack of dietary nitrate, dilution of the nitrite in the urine (such as with diuretics), or non-nitrate-reducing bacteria including Staphylococcus, Enterococcus, or Pseudomonas 16 . VanNostrand and colleagues 17 found that 78.9% of samples containing nitrate-reducing bacteria were actually negative for nitrite on the urine dipstick. Therefore the presence of nitrite has a high positive predictive value of 94% 18 , but in the absence of urinary nitrite a UTI cannot be ruled out.…”
Section: Urinalysis Part 1: Urine Dipstickmentioning
confidence: 99%
“…The dip stick method used in many centres serves only as a screening method but culture is needed for final diagnosis. 7 In almost all cases of nosocomial UTI, there is a need to start treatment before the final microbiological results are available. Area-specific monitoring studies aimed to gain knowledge about the types of pathoges responsible for UTIs and their resistance pattern may help the clinician to choose the correct empirical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Dipstick tests have taken the place of urinary microscopy because the use of the former is very easy and is cheaply available (8,9). LE and nitrite positivity are stated to be good predictors in UTI diagnosis (10)(11)(12). In our study, the relationship between nitrite positivity and reproduction in cultures was found to be stronger than that with LE positivity.…”
Section: Discussionmentioning
confidence: 47%